Informational Nudges to Encourage Pro-environmental Behavior: Examining Differences in Message Framing and Human Interaction - Nelson, Katherine M.; Bauer, Mirja Kristina; Partelow, Stefan (Frontiers in Communication, 2021)
Two natural field experiments were implemented to examine the influence of framing effects on environmental behavior. The first study examined plastic bag use at a convenience store using low cost nudges: an informational message on a sign and interpersonal communication at check-out. We employed a 3x2 treatment design (positive message vs. negative message vs. no sign; each paired with both asking for bag vs. not asking for bag) and report the observed plastic bag use behavior. A second study was conducted using a pre-snorkel briefing with two message frames - positive, negative, and no briefing (control). Environmentally damaging snorkel behavior was anonymously observed and recorded. Both experiments show the same general result: a significant and positive difference between subjects that were exposed to an intervention compared to those in the control conditions. However, we do not find significant differences in observed environmental behavior between the negative and positive framing.